2015
DOI: 10.1123/jab.2014-0102
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Headform Accelerations Associated with Stick Checks in Girls’ Lacrosse

Abstract: Girls' lacrosse is fundamentally a different sport than boys' lacrosse, and girls are not required to wear protective headgear. Recent epidemiological studies have found that stick checks are the leading cause of concussion injury in girls' lacrosse. The purpose of this study was to determine stick check speeds and estimate the head acceleration associated with direct checks to the head. In addition, we briefly examine if commercially available headgear can mitigate the accelerations. Seven (n = 7) experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…While the vast majority of head impacts do not result in concussion, the hypothesized short-term and long-term detrimental effects of subconcussion on brain function 4, 25, 43 and structure, 14, 32 coupled with their proposed role in increasing susceptibility to neurodegenerative disorders, 28, 38 suggest that quantification of subconcussion in a sport may be important for assessing the sport’s overall safety. Previous studies have tried to estimate the frequency and severity of subconcussive head impacts in lacrosse from analysis of biomechanical reconstructions 10 and video capture of live events. 8, 29 This is the first study to directly quantify subconcussive head impacts in live action collegiate lacrosse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the vast majority of head impacts do not result in concussion, the hypothesized short-term and long-term detrimental effects of subconcussion on brain function 4, 25, 43 and structure, 14, 32 coupled with their proposed role in increasing susceptibility to neurodegenerative disorders, 28, 38 suggest that quantification of subconcussion in a sport may be important for assessing the sport’s overall safety. Previous studies have tried to estimate the frequency and severity of subconcussive head impacts in lacrosse from analysis of biomechanical reconstructions 10 and video capture of live events. 8, 29 This is the first study to directly quantify subconcussive head impacts in live action collegiate lacrosse.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using helmet-based accelerometers indicate that collegiate football players can have more than a thousand head impacts in a typical season, 22 but the frequency and severity of head impact experienced by a typical lacrosse player remain unknown. Some studies of head impact in lacrosse have attempted to infer similar data from laboratory-based biomechanical reconstructions 10 or video capture of live lacrosse play. 8, 29 Recent advances in biomechanical sensor technology have miniaturized accelerometers enough that they can be unobtrusively attached to the mastoid process with an adhesive patch, theoretically expanding the number of sports in which head impact can be measured during live play.…”
mentioning
confidence: 99%
“…13,34-52 A much smaller number of studies have quantified head impact in soccer and lacrosse, primarily using self-report questionnaires, 15 video analysis, 31,53,54 and/or laboratory simulations/recreations. [55][56][57][58][59] No published studies present live play biomechanical data in lacrosse, and only one study has reported head impact measured during live play in soccer. 60 No studies have quantified subconcussion in multiple sports with the same biomechanical sensor and directly compared the sports' quantity and severity of head impacts.…”
mentioning
confidence: 99%
“…Anthropometric test device headforms are frequently used in a broad range of head impact research, ranging from the design and evaluation of helmets and headgear [1] to investigations of blast-related brain injury [2]. While several headforms have been used to investigate head impact in sport [3][4][5][6][7], the Hybrid III headform is one of the most frequently encountered in the literature [8,9]. The Hybrid III headform, like all others, features rigid elements to which sensors are mounted.…”
Section: Introductionmentioning
confidence: 99%